Church Politics in Mid-Victorian Britain - Turner, Michael J. author. aut Link
VI, 360 p. 1 illus.
Keywords: This book is a new and original study of High Church activism in the middle decades of the nineteenth century. Focusing on the church union movement, it describes and explains unprecedented levels of clerical-lay cooperation in campaigns of Church defense, responses to contemporary pressures inside the Church, and efforts to mitigate problems in Church-state relations. It explores the leadership role of the London Union on Church Matters and the main factors that shaped its activities, especially Tractarianism, the sense that the Church did not have a sufficiently strong representative voice in debates about questions that directly affected it, and political and social developments that threatened the status and influence of the Church. Michael J. Turner is Roy Carroll Distinguished Professor of British History at Appalachian State University, North Carolina, USA.